Design and experimental characterization of a NiTi-based, high-frequency, centripetal peristaltic actuator. (3rd February 2015) - Borlandelli, E; Scarselli, D; Nespoli, A; Rigamonti, D; Bettini, P; Morandini, M; Villa, E; Sala, G; Quadrio, M
Abstract: Development and experimental testing of a peristaltic device actuated by a single shape-memory NiTi wire are described. The actuator is designed to radially shrink a compliant silicone pipe, and must work on a sustained basis at an actuation frequency that is higher than those typical of NiTi actuators. Four rigid, aluminum-made circular sectors are sitting along the pipe circumference and provide the required NiTi wire housing. The aluminum assembly acts as geometrical amplifier of the wire contraction and as heat sink required to dissipate the thermal energy of the wire during the cooling phase. We present and discuss the full experimental investigation of the actuator performance, measured in terms of its ability to reduce the pipe diameter, at a sustained frequency of 1.5 Hz. Moreover, we investigate how the diameter contraction is affected by various design parameters as well as actuation frequencies up to 4 Hz. We manage to make the NiTi wire work at 3% in strain, cyclically providing the designed pipe wall displacement. The actuator performance is found to decay approximately linearly with actuation frequencies up to 4 Hz. Also, the interface between the wire and the aluminum parts is found to be essential in defining the functional performance of the actuator.